The Role of MicroRNAs in Mitochondria-Mediated Eye Diseases - Carrella, Sabrina; Massa, Filomena; Indrieri, Alessia (Frontiers in Cell and Developmental Biology, 2021)
The retina is among the most metabolically active tissues with high-energy demands. The peculiar distribution of mitochondria in cells of retinal layers is necessary to assure the appropriate energy supply for the transmission of the light signal. Photoreceptor cells (PRs), retinal pigment epithelium (RPE) and retinal ganglion cells (RGCs) presents a great concentration of mitochondria that makes them particularly sensitive to mitochondrial dysfunction. To date, visual loss has been extensively correlated to defective mitochondrial functions. Many Mitochondrial Diseases (MDs) show indeed neuro-ophthalmic manifestations, including retinal and optic nerve phenotypes. Moreover, abnormal mitochondria functions are frequently found in the most common retinal pathologies, i.e., Glaucoma, Age-related Macular Degeneration (AMD) and Diabetic Retinopathy (DR) that share clinical similarities with the hereditary primary MDs. MicroRNAs (miRNAs) are established as key regulators of several developmental, physiological and pathological processes. Dysregulated miRNA expression profiles in retinal degeneration models and in patients underline the potentiality of miRNAs modulation as possible gene/mutation-independent strategy in retinal diseases and highlight their promising role as diseases predictive or prognostic biomarkers. In this review we will summarize the current knowledge about the participation of miRNAs in both rare and common mitochondria-mediated eye diseases. Definitely, given the involvement of miRNAs in retina pathologies and therapy as wells as their use as molecular biomarkers they represent a determining target for clinical applications.